Lords of the Lord: Crossing Boundaries between Human and Divine in Tamil Vaiṣṇava Bhakti Poetry - Jacek Woźniak (Ksiegarnia Akademicka Publishing, 2019)
In the Tamil Bhakti tradition the devotees are generally referred to as ‘servants/slaves [of God],’ and this slave attitude is one of the main characteristics of their relation with God, their Lord. However, in the works of the āḻvārs, Tamil Vaiṣṇava poet-saints, one can find a few examples of the rather unusual situation in which devotees are presented not as slaves of God but actually as His Lords. Thus, exercising their authority over God, who is seemingly dependent on human actions, can be understood as a peculiar way of crossing traditionally recognized boundaries that exist between these two different realms (soul vs. God/human vs. divine). All these acts are supposed to be primarily the expressions of human love and the irresistible need to unite with the Lord, which eventually results in taking control over Him.